Classification of textual data coupled with Machine learning Techniques. (International Journal of Food and Nutritional Sciences, 2022)
The penetration of internet usage has increased dramatically over the last four months as a result of the ongoing pandemic. Indeed, the widespread availability and use of the internet have revolutionized various aspects of our lives. The internet has provided numerous opportunities and services for individuals, businesses, and organizations across different sectors. This unanticipated rise in internet users has resulted in an increase in the number of cunning people. Today, maintaining inclusive and positive interactions is the top responsibility for every supplier of internet platforms. The finest example that can be utilized is Twitter, a platform for online media where users may share their thoughts. Numerous people have already visited this website.